2016
DOI: 10.1007/s00520-016-3334-8
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric assessment factors are associated with mortality after hospitalization in older adults with cancer

Abstract: Purpose Survival in older adults with cancer varies given differences in functional status, comorbidities, and nutrition. Prediction of factors associated with mortality, especially in hospitalized patients, allows physicians to better inform their patients about prognosis during treatment decisions. Our objective was to analyze factors associated with survival in older adults with cancer following hospitalization. Methods Through a retrospective cohort study, we reviewed 803 patients who were admitted to Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…15,18,44 In accordance with our first analyses, most studies have focused on the most prognostic individual GA components to improve the identification of patients with an increased mortality risk for appropriate interventions. 15,18,44 In accordance with our first analyses, most studies have focused on the most prognostic individual GA components to improve the identification of patients with an increased mortality risk for appropriate interventions.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…15,18,44 In accordance with our first analyses, most studies have focused on the most prognostic individual GA components to improve the identification of patients with an increased mortality risk for appropriate interventions. 15,18,44 In accordance with our first analyses, most studies have focused on the most prognostic individual GA components to improve the identification of patients with an increased mortality risk for appropriate interventions.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have evaluated the association between GA and mortality in patients with cancer for different purposes. 15,18,44 In accordance with our first analyses, most studies have focused on the most prognostic individual GA components to improve the identification of patients with an increased mortality risk for appropriate interventions. From these analyses, it can be concluded that GA has some prognostic value, but because of inconsistent results, no specific recommendations can be made to guide treatment decision making.…”
Section: Discussionmentioning
confidence: 62%
“…Dependency, impaired mobility, comorbidities and cognitive impairment are known to have a negative effect on the overall mortality of older patients with cancer, but not on cancer mortality 9,10,12,13,24–26 . This study is therefore the first to highlight an association with cancer death.…”
Section: Discussionmentioning
confidence: 69%
“…The data in the literature show that elderly cancer patients more frequently may have the following problems: increased risk of therapy toxicity, risk of hospitalization, total dependence on the caregiver, reduced motivation for treatment, and difficulty in reaching the treatment center [24]. However, tolerability to active cancer improves for elderly patients by integrating early supportive care.…”
Section: Discussionmentioning
confidence: 99%